Iron status and anaemia of chronic disease in HIV-infected African women in Mangaung, Bloemfontein - Corinna M. Walsh; Zorada Hattingh; Frederick J. Veldman; Christina J. Bester (South African Family Practice)
Background: Anaemia occurs widely among people living with HIV/AIDS. The aim of this study was to investigate the effect of HIV status on iron status, more specifically to investigate the nutritional health of women between 25 and 44 years of age. Methods: An epidemiological study was undertaken in Mangaung, a black residential community of Bloemfontein in the Free State (South Africa). A random sample consisted of 500 women in two age groups (25–34 [n = 273] and 35–44 years [n = 215]). Blood specimens were collected in ethyldimethylacetic acid collection tubes according to standard procedures. Respondents fasted overnight, abstained from exercise and avoided consuming alcohol and caffeine for 24 hours prior to collection of the blood specimens. All specimens were taken in the morning. A full blood count was performed using a Coulter Microdiff 18 Cell Counter. The metabolic variables haematocrit (Hct) and haemoglobin (Hb) were determined. The red blood cell count was performed to calculate the mean corpuscular volume, mean corpuscular haemoglobin (MCH) and mean corpuscular haemoglobin concentration. Age and HIV-status groups were described and compared by non-parametric methods. A p-value lower than 0.05 was considered significant. HIV-infected and -uninfected groups were compared by 95% confidence intervals for the difference in the percentage of women with parameters below or above the normal range.